2022
DOI: 10.3390/s22041443
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Adaptive Functional Electrical Stimulation Kinesitherapy Can Promote the Restoring of Physiological Muscle Synergies for Neurological Patients

Abstract: Background: Neurological diseases and traumas are major factors that may reduce motor functionality. Functional electrical stimulation is a technique that helps regain motor function, assisting patients in daily life activities and in rehabilitation practices. In this study, we evaluated the efficacy of a treatment based on whole-body Adaptive Functional Electrical Stimulation Kinesitherapy (AFESK™) with the use of muscle synergies, a well-established method for evaluation of motor coordination. The evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Next, the paper “Whole-Body Adaptive Functional Electrical Stimulation Kinesitherapy Can Promote the Restoring of Physiological Muscle Synergies for Neurological Patients” [ 9 ] introduces a novel treatment approach, Adaptive Functional Electrical Stimulation Kinesitherapy (AFESK™), for neurological patients using whole-body adaptive functional electrical stimulation kinesitherapy. This treatment shows promise in restoring physiological muscle synergies, enhancing motor functionality, and improving rehabilitation outcomes.…”
Section: Biomedical Sensors For Neurological and Rehabilitation Asses...mentioning
confidence: 99%
“…Next, the paper “Whole-Body Adaptive Functional Electrical Stimulation Kinesitherapy Can Promote the Restoring of Physiological Muscle Synergies for Neurological Patients” [ 9 ] introduces a novel treatment approach, Adaptive Functional Electrical Stimulation Kinesitherapy (AFESK™), for neurological patients using whole-body adaptive functional electrical stimulation kinesitherapy. This treatment shows promise in restoring physiological muscle synergies, enhancing motor functionality, and improving rehabilitation outcomes.…”
Section: Biomedical Sensors For Neurological and Rehabilitation Asses...mentioning
confidence: 99%
“…Among the most used techniques are: mirror therapy, virtual reality or augmented reality [4]. Although it has been studied less, it has also been shown that the use of electrical stimulation could help improve MI parameters in this type of pathologies [5].…”
Section: Introductionmentioning
confidence: 99%